MANTRA STRUCTURE OF BANTEN AND ITS IMPLICATION IN LITERARY LEARNING - Agus Sulaeman; Zainal Rafli; Aceng Rahmat (Universitas PGRI Sumatera Barat, 2018)
Agus Sulaeman, Zainal Rafli, Aceng RahmatTangerang Muhammadiyah University, Banten Indonesia.Jakarta State University, Jakarta Indonesiasultanwahyu13@gmail.com.The purpose of this study is to describe the mantra of Tangerang community at Banten regency.The method in this study uses a qualitative approach with ethnography method. Ethnography method is one of qualitative research strategies in which researcher investigates a cultural group of a natural environment in a long period through primary data collection. The data in this research is in the form of old poetry (mantra) which got from 29respondents from 29 districts in Tanggerang regency. To analyze the data, the researcher used domain analysis, taxonomic analysis, and component analysis. From the research results obtained that the data are in the form of elementary constructive structures such as rhyme, diction,imagyand language figurative. The results of this study can be utilized for literary materials especially in literary studies.